Development and feasibility testing of an evidence-based training programme for pharmacist independent prescribers responsible for the medicines-related activities within care homes. (21st May 2021) - Wright, David J; Blyth, Annie; Maskrey, Vivienne; Norris, Nigel; Bond, Christine M; Hughes, Carmel M; Alldred, David P; Holland, Richard C; ,
Abstract: Introduction: The UK pharmacists with independent prescribing rights (pharmacist independent prescribers [PIPs]) are authorised to prescribe within their areas of competence. To enable PIPs to provide pharmaceutical care to residents in care homes and assume responsibility for medicines management, a process for development and assessment of competence is required. The aim of this research was to develop a training and accreditation process (training programme) to enable PIPs to operate safely and effectively within care homes. Methods: Located in England, Scotland and Northern Ireland across four sites and based on a systematic review, it consisted of four phases: (1) initial stakeholder engagement, (2) uni-professional focus groups and interviews, (3) expert panel consensus and (4) feasibility testing. Four PIPs were trained each to provide pharmaceutical care to 10 care home residents. An expert panel synthesised the evidence at each stage to develop each iteration of the training programme. Content analysis was used throughout. Results: Differences in baseline knowledge of PIPs required inclusion of a Personal Development Framework and the provision of a mentor. Face-to-face training focussed on managing medicines for a complex older person, minimising prescribing costs and supporting people without capacity. Provision of time to understand local context and develop relationships with care homes and general practitioners was identified as a central requirement. PIPs were assessed for competency via viva. Feasibility testing demonstrated that the derived training programme was acceptable, practical and effective. Discussion: The model seemed to work, but due to small numbers, larger-scale testing of the training programme is now required.